2016
DOI: 10.1016/j.jmva.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Weak convergence of discretely observed functional data with applications

Abstract: A general result on weak convergence of the empirical measure of discretely observed functional data is shown. It is applied to the problem of estimation of functional mean value, and the problem of consistency of various types of depth for functional data. Counterexamples illustrating the fact that the assumptions as stated cannot be dropped easily are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…With (A6) we are able to formulate the consistency result also for depths based on noisy observations. This theorem substantially improves on the related consistency results for discretely observed noiseless random functions in C ([0, 1]) provided in Nagy et al (2016a).…”
Section: Depth Functionals Insupporting
confidence: 76%
See 1 more Smart Citation
“…With (A6) we are able to formulate the consistency result also for depths based on noisy observations. This theorem substantially improves on the related consistency results for discretely observed noiseless random functions in C ([0, 1]) provided in Nagy et al (2016a).…”
Section: Depth Functionals Insupporting
confidence: 76%
“…The choice σ 2 ≡ 0 covers the case when the random functions are observed discretely without noise. This setup was considered by Nagy et al (2016a) in the space C ([0, 1]), and in the present contribution we extend these results substantially to discontinuous functions contaminated with measurement errors, using very different proof techniques.…”
Section: Weak Convergence For Noisy Functional Datamentioning
confidence: 65%
“…Nagy et al (2016) used piecewise linear interpolation as described in Lemma 2 to obtain continuous versions of densely observed curves. Therein, it is shown that basing statistical inference on a sample of curves X 1 , .…”
Section: Law Of Large Numbers For Discretely Observed Random Functionsmentioning
confidence: 99%
“…If L k is selected from M k , then, as in Corollary 1, the Bayes risk is achieved with respect to the empirical distributions. Theorem 1(ii) of Nagy & Gijbels & Hlubinka (2015) says that under the above sampling scheme it holds P [G 0,k → G 0 weakly] = 1 and P [G 1,k → G 1 weakly] = 1.…”
Section: Functional Optimalitymentioning
confidence: 99%